Surfactant‐Modified Soil Amendments Reduce Nitrogen and Phosphorus Leaching in a Sand‐Based Rootzone. Issue 5 (1st September 2016) - Shaddox, Travis W.; Kruse, Jason K.; Miller, Grady L.; Nkedi‐Kizza, Peter; Sartain, Jerry B.
Abstract : United States Golf Association putting greens are susceptible to nitrogen (N) and phosphorus (P) leaching. Inorganic soil amendments are used to increase moisture and nutrient retention and may influence N and P leaching. This study was conducted to determine whether N and P leaching could be reduced using soil amendments and surfactant‐modified soil amendments. Treatments included a control (sand), sand–peat, zeolite, calcined clay, hexadecyltrimethylammonium–zeolite, and hexadecyltrimethylammonium–calcined clay. Lysimeters were filled with a 30‐cm rootzone layer of sand–peat (85:15 by volume), below which a 5‐cm treatment layer of amendments was placed. A solution of NO3 –N, NH4 –N, and orthophosphate‐P (2300, 2480, and 4400 μg mL −1, respectively) was injected at the top of each lysimeter, and leachate was collected using an autocollector set to collect a 10‐mL sample every min until four pore volumes were collected. Uncoated amendments, sand, and peat had no influence on NO3 –N retention, whereas hexadecyltrimethylammonium‐coated amendments reduced NO3 –N leaching to below detectable limits. Both coated and uncoated amendments reduced NH4 –N leaching, with zeolite reducing NH4 –N leached to near zero regardless of hexadecyltrimethylammonium coating. Pure sand resulted in a 13% reduction of applied orthophosphate‐P leaching, whereas peat contributed to orthophosphate‐P leaching. Surfactant‐modified amendments reduced orthophosphate‐P leaching by as much as 97%. Surfactant‐modified soil amendments can reduce NO3 –N, NH4 –N, and orthophosphate‐P leaching and, thus, may be a viable option for removing leached N and P before they enter surface or ground waters. Core Ideas: Soil amendments did not reduce NO3 –N leaching. Modified soil amendments reduced NO3 –N, NH4 –N, and orthophosphate‐P leaching. Zeolite was most effective at reducing NH4 –N leaching.